2006
DOI: 10.1897/05-285r.1
|View full text |Cite
|
Sign up to set email alerts
|

Watershed‐based sources of polycyclic aromatic hydrocarbons in urban storm water

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are carcinogenic and mutagenic compounds, ubiquitous in the air and water of urban environments, and have been shown to accumulate in coastal estuarine and marine sediments. Although previous studies have documented concentrations and loads of PAHs in urban runoff, little is known about the sources and temporal patterns of PAH loading from storm water. This study characterized the sources and temporal patterns of PAHs in urban storm water by analyzing PAH concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 37 publications
9
65
0
Order By: Relevance
“…Since more than 90% of all stormwater particles are expected in the 1 to 100 µm range and, given the observed higher concentrations of PAHs in the smaller sediment particles, most of the stormwater runoff PAH load would be expected to be associated with the finer particles. This is similar to findings by Stein et al [4], who observed a strong and consistent pattern of high PAH concentrations in dissolved and fine particulate matter. Stein also found that between 30 and 60% of the total PAH load was discharged in the first 20% of the runoff volume for the studied storms and location.…”
Section: -90supporting
confidence: 92%
See 1 more Smart Citation
“…Since more than 90% of all stormwater particles are expected in the 1 to 100 µm range and, given the observed higher concentrations of PAHs in the smaller sediment particles, most of the stormwater runoff PAH load would be expected to be associated with the finer particles. This is similar to findings by Stein et al [4], who observed a strong and consistent pattern of high PAH concentrations in dissolved and fine particulate matter. Stein also found that between 30 and 60% of the total PAH load was discharged in the first 20% of the runoff volume for the studied storms and location.…”
Section: -90supporting
confidence: 92%
“…According to Metre et al [1], PAH levels in urban freshwater sediments in North America have increased over time, indicating additional discharges associated with industrialization and urbanization, including increased use of vehicles and wear and tear of asphalt [1][2][3]. For example, Stein et al [4] found PAHs in storm fluxes ranged from 1.3 g/km 2 for the largely undeveloped Arroyo Sequit watershed to 224 g/km 2 for the highly urbanized Verdugo Wash watershed in California, USA. Similarly, according to Huston et al [5], there is an increase in the PAHs and other contaminant flux in traffic and industrial areas compared to outer suburbs, implicating these developments positively influencing PAHs contribution in the runoff.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that there are known over 300 compounds from this group, only 16 of them are designated the most common [11]. PAHs are included into a group of primary environmental pollutants due to the toxic, mutagenic and carcinogenic properties [2,6,13,14]. The occurrence of these compounds in groundwater and surface water has been confirmed by many authors [10,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The weight of evidence to date therefore suggests that coho are dying from exposure to chemical pollutants in nonpoint source urban runoff. Urban stormwater contains a very diverse mix of contaminants (Eriksson et al 2007), including metals (Tiefenthaler et al 2008), polycyclic aromatic hydrocarbons (Stein et al 2006), pesticides (Hoffman et al 2000), and other chemicals. The precise agent, whether alone or as a component of a chemical mixture, that causes coho PSM has not yet been identified and is the focus of ongoing investigation.…”
Section: Introductionmentioning
confidence: 99%